1996
DOI: 10.1074/jbc.271.13.7860
|View full text |Cite
|
Sign up to set email alerts
|

Examining Rhodopsin Folding and Assembly through Expression of Polypeptide Fragments

Abstract: The cytosolic space of cells is an important but relatively inaccessible target for the delivery of therapeutic macromolecules. Here we describe the efficient delivery of macromolecules into the cytosolic space of macrophages from liposomes that contain listeriolysin O (LLO), the hemolytic protein of Listeria monocytogenes that normally mediates bacterial passage from phagosomes into cytosol. LLO was purified and encapsulated inside pH-sensitive liposomes, along with other molecules to be delivered. When inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 59 publications
3
70
1
Order By: Relevance
“…These results suggest a sequential and regulated movement of newly synthesized membrane proteins from Sec61p and translocatingchain-associating membrane proteins to chaperones such as calnexin. Functional expression of complementary fragments of polytopic membrane proteins, including AE1 (55,(74)(75)(76)(77)(78)(79), suggests that the final folding likely occurs in the lipid bilayer and supports the "two-stage model" of membrane proteins assembly (33). In this process, the transient interaction with chaperones may be a required step to prevent aggregation and nonspecific interactions between the incompletely folded membrane proteins that are released from the translocon.…”
Section: N-glycosylation-dependent Interaction Of Calnexin Withmentioning
confidence: 75%
“…These results suggest a sequential and regulated movement of newly synthesized membrane proteins from Sec61p and translocatingchain-associating membrane proteins to chaperones such as calnexin. Functional expression of complementary fragments of polytopic membrane proteins, including AE1 (55,(74)(75)(76)(77)(78)(79), suggests that the final folding likely occurs in the lipid bilayer and supports the "two-stage model" of membrane proteins assembly (33). In this process, the transient interaction with chaperones may be a required step to prevent aggregation and nonspecific interactions between the incompletely folded membrane proteins that are released from the translocon.…”
Section: N-glycosylation-dependent Interaction Of Calnexin Withmentioning
confidence: 75%
“…DISCUSSION Few attempts have been made to prepare and characterize peptides corresponding to more than one domain of a GPCR. Notable exceptions are the reconstitution studies on parts of bacteriorhodopsin, rhodopsin, and Ste2p (27)(28)(29). Although these studies expressed, and in some cases isolated, long pieces of these heptahelical proteins, no detailed biophysical analyses were conducted.…”
Section: Analysis Of Peptidesmentioning
confidence: 99%
“…Besides the heptahelical membrane proteins BR (7)(8)(9)(10)(11)27), rhodopsin (28,29), adrenergic receptor (30), and muscarinic acetylcholine receptor (31), such studies also include members of other protein families that form helical bundle structures, like the voltagegated sodium channel (32), yeast a-factor transporter (33), or lactose permease (34). Specifically, in the case of BR it has been shown that proteolytic fragments comprising the two helices AB 2 or FG reassociate with the complementary five-helix fragments CG or AE, respectively, to form the native chromophore (7)(8)(9)27).…”
Section: Bacteriorhodopsin (Br)mentioning
confidence: 99%